Logging software upgrade - Nevalainen, Ari (My University, 2023)
Vaisala weather instruments testing requires data logging to produce information for decisions making. Data logging is increasingly becoming database focused. Database logging was not usable and available to all users easily, for which reason this thesis aimed to bring database logging into internally used logging software. VB.NET based software was to be updated bringing database logging available to all users. The thesis and development of the software update used empirical research. Software principles were applied from theoretical literacy sources. Not all theoretical principles were applied to the internal software. Most software acceptance requirements were met, and software was evaluated acceptable to use. Especially its productivity was remarkable. However, its development should continue to bring all evaluation subjects to fully satisfying level. Some erroneous issues can escalate in wider use. The software was successfully updated, and it began a new era in its development lifecycle. Software was uploaded into GIT and should continue to be improved to better serve the company and its needs.
Keywords: Vaisala, weather instruments, testing, logging, InfluxDB, Grafana